2015
DOI: 10.3390/foods4040654
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of R5 and G12 Antibody-Based ELISA Used for the Determination of the Gluten Content in Official Food Samples

Abstract: Celiac Disease (CD) is one of the most common food intolerances. It comes along with serious damage of the mucosa in the small intestine and is caused by the storage proteins—termed “gluten”—of wheat, rye, barley and possibly oats. Sensitive individuals need to stick to a strict gluten-free diet. The gluten level in food products labeled as “gluten-free”, must not exceed 20 mg/kg. It is obvious that effective test methods are needed to accurately determine the gluten concentration in foods. The determination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 3 publications
(3 reference statements)
2
27
0
Order By: Relevance
“…At the moment, the R5 Mendez method is recommended as type 1 method for the determination of gluten (Codex Standard 234-1999, but due to recent progress in method development and validation studies (Don et al 2014), efforts are underway to review this recommendation and add the G12 mAb-based method or others (Codex Committee of Methods of Analysis and Sampling 2015). A recent comparison of results obtained with the G12 compared to the R5 ELISA concluded that both assays gave comparable gluten contents in a variety of routine food samples (Hochegger et al 2015). The aforementioned study did not include any WSt samples, but the data presented here indicated that the R5 and G12 assays yielded significantly different gluten contents in 23 out of a total of 31 WSt, including the control sample (W9 + 20).…”
Section: Discussionmentioning
confidence: 58%
“…At the moment, the R5 Mendez method is recommended as type 1 method for the determination of gluten (Codex Standard 234-1999, but due to recent progress in method development and validation studies (Don et al 2014), efforts are underway to review this recommendation and add the G12 mAb-based method or others (Codex Committee of Methods of Analysis and Sampling 2015). A recent comparison of results obtained with the G12 compared to the R5 ELISA concluded that both assays gave comparable gluten contents in a variety of routine food samples (Hochegger et al 2015). The aforementioned study did not include any WSt samples, but the data presented here indicated that the R5 and G12 assays yielded significantly different gluten contents in 23 out of a total of 31 WSt, including the control sample (W9 + 20).…”
Section: Discussionmentioning
confidence: 58%
“…Other research groups have recently compared the performance of the different antibodies [56][57][58][59] on several food matrices, from grains of different species (e.g., wheat, rye and barley) to fermented-hydrolyzed foods.…”
Section: Type Of Antibody In Immunological Assaysmentioning
confidence: 99%
“…It is a shared position within the scientific community that the identification of the most suitable sample preparation and extraction procedure is one more critical point in gluten determination [32,33,59]. It is known that the main requirement for immunological assays is, in fact, that they should be able to measure the toxic proteins, regardless of the type of food (raw material or heat-treated and enzymatically-treated product).…”
Section: Gluten Extraction Procedures In Immunological Assaysmentioning
confidence: 99%
See 2 more Smart Citations